Implementation of Pioneering Sea Transportation in the Regional Transportation Office of the North Sulawesi Province - Stenly Patimbano; Evi Elvira Masengi; Laurens Bulo (Technium Social Sciences Journal, 2025)
The purpose of the research is to find out, analyze and describe the Policy on the Implementation of Pioneer Sea Transportation at the Regional Transportation Office of North Sulawesi Province. The method used in this research is qualitative research method. The data sources in this research are informants, events or activities and documentation. Data collection techniques in this study were in-depth interviews, observation and documentation. Meanwhile, the data analysis technique uses an interactive model with components, namely data collection, data display, condensation and verification. The results showed that the implementation of digital-based information systems for pioneer ship services faced several obstacles, mainly due to the uneven internet network in the North Sulawesi region. The lack of inter-island potential data is a major obstacle in determining the priority of ship routes in pioneer sea transportation services. The absence of government officers who supervise directly on board during the trip is due to the absence of a budget to finance personnel assignments. The availability of the budget for pioneer sea transportation in North Sulawesi still focuses on operational costs and routine maintenance of ships. The lack of synchronization between agencies, limited communication with the central government, and unoptimal collaboration with the private sector and the community, such as the lack of synchronization in program planning, implementation, and evaluation make coordination between agencies in the implementation of pioneer sea transportation in North Sulawesi less than optimal.